2016
DOI: 10.12952/journal.elementa.000112
|View full text |Cite
|
Sign up to set email alerts
|

Air-ice carbon pathways inferred from a sea ice tank experiment

Abstract: Given rapid sea ice changes in the Arctic Ocean in the context of climate warming, better constraints on the role of sea ice in CO 2 cycling are needed to assess the capacity of polar oceans to buffer the rise of atmospheric CO 2 concentration. Air-ice CO 2 fluxes were measured continuously using automated chambers from the initial freezing of a sea ice cover until its decay during the INTERICE V experiment at the Hamburg Ship Model Basin. Cooling seawater prior to sea ice formation acted as a sink for atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 65 publications
(118 reference statements)
2
15
0
Order By: Relevance
“…In situ and temperature-controlled short-term radiotracer incubations identified a significant correlation between sea-ice temperature and intracellular iron uptake by Antarctic sea-ice algae as well as indications of luxury iron uptake (Lannuzel et al, 2017). Sea-ice tank experiments showed that sea ice is a source of CO 2 during ice formation and a sink during ice-melt periods, with a suggested role for gas-bubble formation to explain the measured outflux of CO 2 (Kotovitch et al, 2016).…”
Section: Process Studies and Modelingmentioning
confidence: 97%
“…In situ and temperature-controlled short-term radiotracer incubations identified a significant correlation between sea-ice temperature and intracellular iron uptake by Antarctic sea-ice algae as well as indications of luxury iron uptake (Lannuzel et al, 2017). Sea-ice tank experiments showed that sea ice is a source of CO 2 during ice formation and a sink during ice-melt periods, with a suggested role for gas-bubble formation to explain the measured outflux of CO 2 (Kotovitch et al, 2016).…”
Section: Process Studies and Modelingmentioning
confidence: 97%
“…We also include three diffusive parameterizations ( Table 2). The first is VC10, retained in spite of its drawbacks because it was used in several biogeochemical studies (Kotovitch et al, 2016;Moreau et al, 2015;Vancoppenolle et al, 2010). We also include J11_EMD and J11_MLD (Jeffery et al, 2011).…”
Section: Implementation Of Parameterizationsmentioning
confidence: 99%
“…A small part of the brine supersaturated in CO 2 is then predicted to be expelled to the sea-ice surface and to release CO 2 to the atmosphere (Rysgaard et al, 2011). Small, positive CO 2 fluxes out of young, newly formed sea ice have indeed been detected in the field (Else et al, 2011;Geilfus et al, 2013;Barber et al, 2014;Nomura et al, 2018) and in artificial sea ice (Nomura et al, 2006;Geilfus et al, 2016;Kotovitch et al, 2016). However, while the CO 2 flux out of the young ice itself is likely positive (upward), the overall CO 2 flux during ice formation in the marginal sea ice zone may be negative, depending on the presence of open water, including leads and polynyas, which may enhance CO 2 uptake from the air (e.g., Anderson et al, 2004;Loose et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TIC and salinity decoupling could be more pronounced in colder, and thus more saline, brine. Nevertheless, experimental and model studies on newly forming sea ice have found that ikaite precipitation and CO 2 outgassing to the atmosphere are small compared to the efflux of dissolved inorganic carbon with brine to the underlying water (Rysgaard et al, 2007;Sejr et al, 2011;Moreau et al, 2015;Kotovitch et al, 2016). This indicates that the transport in dissolved form is predominant, and the TIC signal should largely follow salinity.…”
Section: Introductionmentioning
confidence: 99%